Imputation of TPMT defective alleles for the identification of patients with high-risk phenotypes - Almoguera, Berta; Vazquez, Lyam; Connolly, John J.; Bradfield, Jonathan; Sleiman, Patrick; Keating, Brendan; Hakonarson, Hakon (Frontiers in Genetics, 2014)
Background: The activity of thiopurine methyltransferase (TPMT) is subject to genetic variation. Loss-of-function alleles are associated with various degrees of myelosuppression after treatment with thiopurine drugs, thus genotype-based dosing recommendations currently exist. The aim of this study was to evaluate the potential utility of leveraging genomic data from large biorepositories in the identification of individuals with TPMT defective alleles. Material and methods: TPMT variants were imputed using the 1,000 Genomes Project reference panel in 87,979 samples from the biobank at The Children’s Hospital of Philadelphia. Population ancestry was determined by principal component analysis using HapMap3 samples as reference. Frequencies of the TPMT imputed alleles, genotypes and the associated phenotype were determined across the different populations. A sample of 630 subjects with genotype data from Sanger sequencing (N=59) and direct genotyping (N=583) (12 samples overlapping in the two groups) was used to check the concordance between the imputed and observed genotypes, as well as the sensitivity, specificity and positive and negative predictive values of the imputation. Results: Two SNPs (rs1800460 and rs1142345) that represent three TPMT alleles (*3A, *3B, and *3C) were imputed with adequate quality. Frequency for the associated enzyme activity varied across populations and 89.36-94.58% were predicted to have normal TPMT activity, 5.3-10.31% intermediate and 0.12-0.34% poor activities. Overall, 98.88% of individuals (623/630) were correctly imputed into carrying no risk alleles (553/553), heterozygous (45/46) and homozygous (25/31). Sensitivity, specificity and predictive values of imputation were over 90% in all cases except for the sensitivity of imputing homozygous subjects that was 80.64%. Conclusion: Imputation of TPMT alleles from existing genomic data can be used as a first step in the screening of individuals at risk of developing serious adverse event